Higher Education in South Sudan: Living with Challenges - Abol Kuyok, Kuyok (International Higher Education, 2017)
This article discusses thevresilience of South Sudan’s higher education system in dealing with colossal challenges that impede its performance. The ability of the universities to endure the underlying problems has potentialities for tertiary institutions in similar contexts.